Enhanced uptake, high selective and microtubule disrupting activity of carbohydrate fused pyrano-pyranones derived from natural coumarins attributes to its anti-malarial potential - Gupta, Sonal (Malar J, 2019)
BACKGROUND: Malaria is one of the deadliest infectious diseases caused by protozoan parasite of Plasmodium spp. Increasing resistance to anti-malarials has become global threat in control of the disease and demands for novel anti-malarial interventions. Naturally-occurring coumarins, which belong to a class of benzo-α-pyrones, found in higher plants and some essential oils, exhibit therapeutic potential against various diseases. However, their limited uptake and non-specificity has restricted their wide spread use as potential drug candidates. METHODS: Two series of carbohydrate fused pyrano[3,2-c]pyranone carbohybrids which were synthesized by combination of 2-C-formyl galactal and 2-C-formyl glucal, with various freshly prepared 4-hydroxycoumarins were screened against Plasmodium falciparum. The anti-malarial activity of these carbohybrids was determined by growth inhibition assay on P. falciparum 3D7 strain using SYBR green based fluorescence assay. Haemolytic activity of carbohybrid 12, which showed maximal anti-malarial activity, was determined by haemocompatibility assay. The uptake of the carbohybrid 12 by parasitized erythrocytes was determined using confocal microscopy. Growth progression assays were performed to determine the stage specific effect of carbohybrid 12 treatment on Pf3D7. In silico studies were conducted to explore the mechanism of action of carbohybrid 12 on parasite microtubule dynamics. These findings were further validated by immunofluorescence assay and drug combination assay. RESULTS: 2-C-formyl galactal fused pyrano[3,2-c]pyranone carbohybrid 12 exhibited maximum growth inhibitory potential against Plasmodium with IC(50) value of 5.861 µM and no toxicity on HepG2 cells as well as no haemolysis of erythrocytes. An enhanced uptake of this carbohybrid compound was observed by parasitized erythrocytes as compared to uninfected erythrocytes. Further study revealed that carbohybrid 12 arrests the growth of parasite at trophozoite and schizonts stage during course of progression through asexual blood stages. Mechanistically, it was shown that the carbohybrid 12 binds to α,β-heterodimer of tubulin and affects microtubule dynamics. CONCLUSION: These findings show carbohydrate group fusion to 4-hydroxycoumarin precursor resulted in pyrano-pyranones derivatives with better solubility, enhanced uptake and improved selectivity. This data confirms that, carbohydrate fused pyrano[3,2-c]pyranones carbohybrids are effective candidates for anti-malarial interventions against P. falciparum.